2010
DOI: 10.1254/jphs.10001sc
|View full text |Cite
|
Sign up to set email alerts
|

15d-Prostaglandin J2 Enhancement of Nerve Growth Factor–Induced Neurite Outgrowth Is Blocked by the Chemoattractant Receptor– Homologous Molecule Expressed on T-Helper Type 2 Cells (CRTH2) Antagonist CAY10471 in PC12 Cells

Abstract: Abstract. The chemoattractant receptor-homologous molecule expressed on T-helper type 2 cells (CRTH2) is the most recently identified prostaglandin (PG) receptor for both PGD 2 and 15-deoxy-Δ 12,14 -PGJ 2 (15d-PGJ 2 ). We examined the mechanism by which 15d-PGJ 2 enhances nerve growth factor (NGF)-induced neurite outgrowth in PC12 cells. CAY10471 (CRTH2 antagonist) inhibited both the neurite-promotion and p38 mitogen-activated protein (MAP) kinase phosphorylation induced by 15d-PGJ 2 . In contrast, 13,14-dihyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…To investigate the role of DP receptors, the DP1 receptor antagonist BW A868C (0.1 and 1 μM) (Hatanaka et al, 2010) and the DP2 receptor antagonist BAY-u3405 (1 and 10 μM) (Zhu et al, 2010) were incubated with primary neurons in combination with 10 and 20 μM PGD 2 . Neuronal cell death was measured 48 h after treatment.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the role of DP receptors, the DP1 receptor antagonist BW A868C (0.1 and 1 μM) (Hatanaka et al, 2010) and the DP2 receptor antagonist BAY-u3405 (1 and 10 μM) (Zhu et al, 2010) were incubated with primary neurons in combination with 10 and 20 μM PGD 2 . Neuronal cell death was measured 48 h after treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The norepinephrine transporter is phosphorylated and activated by p38-MAP kinase, leading to the rapid clearing of synaptic NE [49]. We recently found that a selective CRTH2 agonist stimulates p38-MAP kinase and enhances NGF-induced neurite outgrowth in PC12 cells [50], suggesting that the CRTH2-mediated pathway may directly regulate NE content through the phosphorylation of the norepinephrine transporter in the hippocampus. In addition, corticotropinreleasing hormone mediates PGD 2 -mediated regulation of NE content [51].…”
Section: Discussionmentioning
confidence: 99%
“…DP1 has been primarily reported to regulate dendritic cell function [44] while DP2 was suggested to promote inflammatory pathways [45]. 13,14-Dihydro-15-keto PGD 2 is a selective DP2 agonist [46], while little information is available about the ability of 15d-PGJ 2 to stimulate DP1 [24] and/or DP2 receptors [47].…”
Section: Discussionmentioning
confidence: 99%